Outside-in stepwise functionalization of mesoporous silica nanocarriers for matrix type sustained release of fluoroquinolone drugs1. Issue 10 (14th March 2015) - Liu, Fang; Wang, Jingnan; Huang, Peilin; Zhang, Qun; Deng, Juntao; Cao, Qingyun; Jia, Jinliang; Cheng, Jianhua; Fang, Yueping; Deng, David Y. B.; Zhou, Wuyi
<x xml:space="preserve">Abstract</x> In this study, we propose outside-in stepwise functionalization of MCM-41-type mesoporous silica for use as a high-efficiency matrix drug delivery nanosystem aimed at the insoluble antibacterial agent fluoroquinolone.